2013
DOI: 10.1007/s00405-013-2841-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cerebrospinal venous insufficiency in patients with Ménière’s disease

Abstract: To analyze the presence of chronic cerebrospinal venous insufficiency parameter and vascular abnormalities, in the internal jugular veins (IJVs) and/or vertebral veins in sitting and supine posture, in patients with Meniere's disease compared to healthy general population. A prospective study on 32 patients affected by definite Ménière was performed from February 2012 to January 2013. All subjects underwent an echo-color Doppler examination of the cerebrospinal venous flow. 21 of the 32 Menieric patients showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 23 publications
3
41
2
Order By: Relevance
“…A first attempt for a rational and scientific approach to this question was recently made by Filipo et al These authors evaluated 32 patients only suffering from MD. They examined the morphological and functional characteristics of the venous vessels of these patients comparing results to data coming from 97 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A first attempt for a rational and scientific approach to this question was recently made by Filipo et al These authors evaluated 32 patients only suffering from MD. They examined the morphological and functional characteristics of the venous vessels of these patients comparing results to data coming from 97 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the distal part of the vein of the vestibular aqueduct in experimental animals causes disturbances in the endolymph homeostasis and potentially symptoms similar to the ones of Ménière's disease [Friis and Qvortrup, 2007], confirming previous observations in humans affected by Ménière's disease who presented with occlusion of the vein of the vestibular aqueduct. Central nervous system vein occlusions seem to play a role in the syndrome; in fact, chronic cerebrospinal vein insufficiency is also significantly increased in Ménière's disease patients [Alpini et al, 2013;Filipo et al, 2015] compared to controls, and preliminary results have shown significant improvement of the symptoms in patients with Ménière's disease and chronic cerebrospinal vein insufficiency treated with percutaneous transluminal angioplasty [Bruno et al, 2013]. Patients with concurrent multiple sclerosis and Ménière's disease, who are treated with percutaneous transluminal angioplasty for multiple sclerosis, may be considered as a potential elite cohort for further studies and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Higher prevalence of CCSVI has been reported not only in MS patients, but also in Parkinson disease, 24 and Meniere disease. 25 Other entities like transient global amnesia and chronic migraine have also been associated with jugular reflux and changes in the venous dynamics. 26,27 Additionally, well-known MS susceptibility factors like cardiovascular, infectious, and inflammatory risks have been associated with increased prevalence of CCSVI.…”
Section: Discussionmentioning
confidence: 99%